Begomoviruses on two chili types in Southeast Sulawesi Indonesia: variation of symptom severity assessment and DNA-betasatellite identification - Taufik, Muhammad; Firihu, Muhammad Zamrun; Hasan, Asmar; HS, Gusnawaty; Variani, Viska Inda; Syair, Syair; Botek, Muhammad (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
The association of viral satellite DNA with Begomoviruses influences symptom expression in infected plants. Normalized Difference Vegetation Index (NDVI) is an image processing method used to assess plant health based on the plant’s ability to absorb sunlight for photosynthesis. Therefore, this study aims to assess symptom severity based on symptom variation and NDVI, as well as to detect and identify the presence of beta-satellite DNA associated with chili plants. The study was conducted in North Kolaka Regency, Southeast Sulawesi Province, Indonesia. It involved observations and image recording of symptom variations in the sampled cayenne and big red chili plants, followed by the detection of beta-satellite DNA in the samples using the polymerase chain reaction (PCR). The results confirmed the presence of non-coding satellite DNA associated with the Pepper yellow leaf curl Indonesia virus (PepYLCIV) in all severe, mild, or asymptomatic plant samples. In the phylogenetic tree, the non-coding satellite DNA isolates from Southeast Sulawesi are included in the betasatellite group and exhibit different genetic characteristics from other isolates available in the GenBank database. The cayenne chili with severe symptoms had lower NDVI values than the mild and asymptomatic categories, indicating that this type of chili with severe symptoms had a lower ability to absorb light. Further studies are needed to characterize the alpha-satellite type in the Southeast Sulawesi region for potential use in cross-protection mechanisms against plant virus infections.